Aplicación de microondas para la elaboración de ciruelas deshidratadas descarozadas sin conservantes - Urfalino, Delia Paola; Daniele, Martin Juan; Worlock, Jesica (Instituto de Tecnología de Alimentos, INTA, 2023)
The present work proposes to modify the obtaining of dehydrated pitted plums without preservatives, replacing the stages of tenderization, pitting and dehydration in belt kiln by exposure to microwaves and subsequent pitting. Through exposure to microwaves, a texture is achieved that allows pitting, without the need to incorporate water into the fruit and avoiding the subsequent stage of dehydration in tape.